Legal paremeters of administration in a democratic society: the case of Australia - Lee, Robert D
Alternative approaches exist for setting legal limits on the powers of government administrators in a democratic society. Australia, starting in the 1970s, launched a set of reforms that has come to be called the "new administrative law". Today, there are 12 major characteristics of the Australian system, some of which are common in the United States, some less common, and some basically not in use. Experience under this system shows positive results, but some troubling aspects of administrative law continue. Reproduced
Keywords: Australia; Administrative Law; Administrative Law - Australia